Questioning Naturalism in 3D User Interfaces. - BOWMAN, DOUG A.; MCMAHAN, RYAN P.; RAGAN, ERIC D. (Communications of the ACM, 2012)
The article looks at the design of three-dimensional (3D) User Interfaces (UIs), such as the controllers used in console gaming systems. Particular emphasis is given to the use of spatial input technology to design 3D UIs that provide a naturalistic experience for users, comparing the user performance and engagement with these devices with traditional UIs. The use of naturalistic UIs in various tasks are analyzed, including viewpoint rotation, object manipulation, and multitasking. It is argued that the level of natural interaction fidelity is an important factor in the evaluation of 3D UIs.